Theoretical Review of Tinnitus and Analysis of the Processing of Signals Generated by the Ear Using Matlab, Adobe Audition y Spectra Plus - Llanos Ávila, Jesús (Ingeniería Solidaria, 2014)
This paper presents the analysis of signals emitted by the ears of patients suffering tinnitus, to establish a possible link with spontaneous otoacoustic emissions that are present in most normal ears. Prior to this analysis, a theoretical review was conducted of otoacoustic emissions, establishing the classes and applications in clinical practice to objectively determine hearing impairment. The basis for this was a set of articles with important scientific content, arrived at through an exhaustive selection process in order to provide a relevant, adequate and concise context. The signals captured and later analyzed correspond to a group of five volunteer patients who suffer from tinnitus. This article is a product of the research study titled “Developing diagnostic equipment to objectively determine tinnitus”, conducted by the “Tinnitus” research group at the La Samaritana hospital. This research has been ongoing since 2006.
Keywords: otoacoustic emissions; analysis; signals; tinnitus